The Mobile Banking Application to Boost Service: How the Elderly Consumers’ Perceptions? - Rosa Rilantiana; Roostikasari Nugraheni (Jurnal Sosial Humaniora, 2023)
This research aims to examine the factors influencing the decision-makingprocess of older individuals when it comes to using electronic bankingservices. While technology plays a crucial role in today's society, it may notbe enough to reach vulnerable populations, particularly the elderly. The studywill utilize the STATA 14.2 program for SEM analysis, employingquantitative analysis to explore decisions related to digital bankingapplications within a sample of 300 individuals aged over 50 in Surabaya.During the Covid-19 pandemic, digital technology served as an operationaltool to mitigate the spread of the virus. However, it is essential to recognizethat technology is a long-term investment, even after the pandemic. Elderlyusers need to be mindful of sudden technological changes and improve theirdigital literacy. This study underscores the importance of understanding thebanking sector when assessing how specific groups, such as the elderly, utilizedigital technologies. Moreover, for business continuity, gaining insights intohow the elderly utilize banking apps is crucial. It is imperative to implementthe necessary support systems and digital infrastructure promptly andeffectively to meet the current and future demands.